New insights on the anatomy and systematics of Kallokibotion Nopcsa, 1923, the enigmatic uppermost Cretaceous basal turtle (stem Testudines) from Transylvania. Issue 2 (31st August 2017) - Pérez-García, Adán; Codrea, Vlad
Abstract: Kallokibotion is a basal turtle (stem Testudines) described almost a century ago from generally poorly preserved specimens, from the Maastrichtian of the Haţeg Basin (Romania). A revision of these specimens, performed almost 25 years ago, allowed a better understanding of the taxon. Kallokibotion has remained an enigmatic form because of the limited number of available characters. However, it has frequently been included in general phylogenetic hypotheses of relationships among Testudinata or among basal forms. The information in these analyses has been based on the classic material because, until now, no new specimens had been figured and described in detail. Its phylogenetic position has been under discussion. Well-preserved new material is presented here. These specimens not only reveal detailed cranial and postcranial elements poorly known until now, refuting previous hypotheses about the anatomy of this taxon, but also allow us to identify numerous hitherto unknown characters. Thus, Kallokibotion is recognized as one of the best-characterized stem Testudines. A new diagnosis for its only known species, Kallokibotion bajazidi, is proposed. The incorporation of new information in several phylogenetic analyses shows Kallokibotion as the sister taxon of the crown Testudines.